2018
DOI: 10.1074/jbc.ra118.003725
|View full text |Cite
|
Sign up to set email alerts
|

VAMP-associated protein-A and oxysterol-binding protein–related protein 3 promote the entry of late endosomes into the nucleoplasmic reticulum

Abstract: The endocytic pathway plays an instrumental role in recycling internalized molecules back to the plasma membrane or in directing them to lysosomes for degradation. We recently reported a new role of endosomes-the delivery of components from extracellular vesicles (EVs) to the nucleoplasm of recipient cells. Using indirect immunofluorescence, FRET, immunoisolation techniques, and RNAi, we report here a tripartite protein complex (referred to as the VOR complex) that is essential for the nuclear transfer of EV-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
98
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(106 citation statements)
references
References 54 publications
8
98
0
Order By: Relevance
“…First, our data with importazole treatment suggest that nuclear pores are involved in this process instead of the nuclear entrapment following the reorganization of the nuclear envelope during mitosis. Second, novel intracellular routes involving endosomal pathways were recently described to explain the nuclear localization of surface proteins (Chaumet et al , ; Santos et al , ). One of them relies on the presence of late endosomes in the nucleoplasmic reticulum where the endocytosed membrane proteins including Prom1 are delivered on the way to the nucleoplasm through the nuclear pores (Santos et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, our data with importazole treatment suggest that nuclear pores are involved in this process instead of the nuclear entrapment following the reorganization of the nuclear envelope during mitosis. Second, novel intracellular routes involving endosomal pathways were recently described to explain the nuclear localization of surface proteins (Chaumet et al , ; Santos et al , ). One of them relies on the presence of late endosomes in the nucleoplasmic reticulum where the endocytosed membrane proteins including Prom1 are delivered on the way to the nucleoplasm through the nuclear pores (Santos et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, novel intracellular routes involving endosomal pathways were recently described to explain the nuclear localization of surface proteins (Chaumet et al , ; Santos et al , ). One of them relies on the presence of late endosomes in the nucleoplasmic reticulum where the endocytosed membrane proteins including Prom1 are delivered on the way to the nucleoplasm through the nuclear pores (Santos et al , ). In these processes, both ubiquitination and the interaction with adaptor protein syntenin‐1 can regulate the intracellular trafficking of Prom1 (Karbanová et al , ; Yang et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…To validate this split-GFP assay as a bonafide strategy for assessing ER-LE contact, we depleted the ER membrane protein VAPA/B and found that the GFP signal was indeed decreased ( Supplementary Fig. 5); VAPA/ B were previously shown to be ER-LE tethering proteins [32][33][34] . Strikingly, depletion of EMC4 and EMC7 also decreased the GFP intensity ( Fig.…”
Section: Resultsmentioning
confidence: 98%
“…While investigating the role of spectrin in endosomal transport in Drosophila we discovered that mSpitz, the membrane bound precursor of the EGF Receptor ligand sSpitz, strongly Floyd Mattie et al p4 accumulates in nuclear envelope invaginations 19 . These structures, called cytoplasmic capes 20 , were originally seen in ultrastructural studies of Drosophila salivary gland nuclei 21 and are distinguished from the nuclear reticulum in scale and morphology 22,23 . We previously demonstrated that these distinctive structures are strongly associate with endosome-like organelles and contain ubiquitylated proteins 19 .…”
Section: Introductionmentioning
confidence: 99%